Artistic Labour of the Body - Gush, Rose-Anne (Historical Materialism Book Series, 2026)
Artistic Labour of the Body examines VALIE EXPORT's and Elfriede Jelinek's use of the body and psyche as artistic material to explore Adorno's concept of artistic labour. By deploying the body as artistic material, their works challenge women's reduction to reproductive function or sexual object, articulating a feminism beyond "innocence". Gush demonstrates how their art critiqued postwar Austria's culture of disavowal, where unprocessed legacies of Nazism perpetuated Austria's victimhood myth, while also exploring the complex identifications within this critique. The book reframes postwar artistic practices that revealed the body as both a site of patriarchal-capitalist violence and of resistance.